What do innovation networks really do for local development? - Nicolas Bonnet (European Regional Science Association (ERSA), 2010)
We address the role of innovation networks on growth of territories in the Canadian space (TER WALL et BOSCHMA, 2009). We rely on an analysis of labor market areas for the period 1996 - 2008 on the basis of patent applications filed jointly by several inventors so as to develop the networks of cooperation. An analysis of such networks on the basis of these geography areas can provide some additional explanatories on the core-periphery model, which appears between the labor market areas that innovate and those that develop economically. The working hypothesis is therefore as follows. If technological change is undeniably the macro-economic factors of growth (ROMER, 1990), the level of flow of knowledge spillover between cities and particularly the degree of centrality of each of them within the collaborative network, has a differential impact on local economic development between urban areas (GORDON et McCANN, 2000). This working hypothesis is based on the observation that innovation at the local level does not necessarily lead to economic development of territories in which it operates.
Keywords: 330